National prevalence and risk factors for tungiasis in Kenya - Elson, L; Kamau, C; Koech, S; Muthama, C; Gachomba, G; Sinoti, E; Chondo, E; Mburu, E; Wakio, M; Lore, J; Maia, M; Adetifa, I; et al. (BioMed Central, 2023)
Background: Tungiasis is a highly neglected tropical skin disease caused by the sand flea, Tunga penetrans, the female of which burrows into the skin, causing pain and itching. The disease occurs throughout South America and sub-Saharan Africa but there are few systematic data on national disease burdens. The tungiasis research community is keen to develop survey methods to fill this gap. Here we used a school-based, thorough examination method to determine the prevalence and risk factors for tungiasis in Kenya. Methods: We conducted the first nationally representative survey of tungiasis, including nine counties covering the major ecological zones of Kenya. A stratified multistage random sampling was used to select 22 primary schools from each of the nine counties and to select up to 114 pupils aged 8 to 14 years in each school. Pupils were examined thoroughly for tungiasis. Two surveys were conducted, the first between May and July 2021 and the second between October 2021 and April 2023 when pupils were also interviewed for risk factors. Mixed effect logistic regression models were used to test associations of independent variables with tungiasis using the school as a random effect. Results: The overall prevalence of tungiasis in the first survey was 1.35% [95% confidence interval (CI): 1.15–1.59%], and 0.89% in the second survey. The prevalence ranged from 0.08% (95% CI: 0.01–0.59%) in Taita Taveta county to 3.24% (95% CI: 2.35–4.44%) in Kajiado county. Tungiasis infection was associated with county of residence, male sex [adjusted odds ratio (aOR) = 2.01, 95% CI: 1.52–2.67], and lower age (aOR = 0.81, 95% CI: 0.75–0.88). For the first time we demonstrate an association with attending public schools rather than private schools (aOR = 5.62, 95% CI: 1.20–26.22) and lower socioeconomic status (aOR = 0.10, 95% CI: 0.03–0.33). Using a rapid screening method of the top of feet only, would have missed 62.9% of all cases, 78.9% of mild cases and 20.0% of severe cases. Conclusions: Tungiasis is widely but heterogeneously distributed across Kenya. School-based surveys offer an efficient strategy for mapping tungiasis distribution.